15 easy & irresistible math mini-books - Crawford, Sheryl Ann.; Sanders, Nancy I. (New York : Scholastic, 2002)
Contains reproducible, easy-to-read stories and activities designed to help students in grades K through two learn basic math skills.
"Grades K-2"--Cover.
"Meets the NCTM standards"--Cover.
"Reproducible, easy-to-read stories and activities that invite kids to add, subtract, measure, tell time, and practice other important early math skills.".
Professional
Keywords: Arithmetic -- Study and teaching (Primary); Creative activities and seat work; Mathematics -- Study and teaching (Primary); Teaching -- Aids and devices; Arithmetic -- Study and teaching; Creative activities; Mathematics -- Study and teaching; Teaching -- Aids and devices